MANAJEMAN SARANA PRSARANA DALAM MEWUJUDKAN PEMBELAJARAN SISWA YANG BERKUALITAS DI MTS MATLAUL ANWAR PAMULANG - Mas’amah Mas’amah; Amaliyah Amaliyah; Irma Nurjanah; Naila Sania; Niken Aulia Pradana (Jurnal Kepemimpinan dan Pengurusan Sekolah, 2026)
This research is motivated by the importance of the quality of learning in madrasah (Islamic schools) being significantly influenced by the management of available facilities and infrastructure. However, at MTS Matlaul Anwar Pamulang, there is a gap between the ideal and the real condition of educational facilities, such as the limited availability of technology-based learning media, extracurricular facilities, and library collections. This study aims to analyze the implementation of facilities and infrastructure management, identify the constraints encountered, and evaluate its impact on student quality. The research employs a descriptive qualitative approach through observation, interviews, and documentation. The results show that the management of facilities and infrastructure has been carried out through planning, procurement, utilization, maintenance, and supervision, although there are still budgetary constraints and facility limitations that affect the effectiveness of their utilization. The gap between the ideal and the real condition can be reduced through needs-based planning, optimal maintenance, and cooperation with the madrasah committee. The impact of this research indicates that effective facilities and infrastructure management contributes to improving the quality of learning and developing students' potential. The findings of this study can serve as a reference for other madrasah in enhancing educational quality through more optimal facilities and infrastructure management